Edukasi Rumah Tahan Gempa dan Mitigasi Bencana (Persiapan Sebelum, Sesaat dan Setelah) Gempa - Rita Mulyandari; Dwi Suranto; Yasin Qhadafi; Iksan Mahendra (LPPM POLITEKNIK LP3I, 2024)
Indonesia is a country vulnerable to earthquakes due to its location along the Pacific Ring of Fire, including the Special Region of Yogyakarta, which is frequently affected by earthquakes with severe impacts. To reduce the risk of injuries and casualties from earthquakes, community preparedness and disaster mitigation education are urgently needed. This community service program was conducted through a community-based approach at the Bumi Damai Shelter Foundation in Yogyakarta, consisting of three phases: preparation, implementation, and evaluation. The activities included developing educational materials on earthquake-resistant buildings and disaster mitigation tailored for children from elementary to high school levels, using interactive methods such as lectures, videos, and earthquake simulations. The evaluation results indicate that the program successfully increased participants' understanding and preparedness for earthquakes, with high enthusiasm observed throughout the activities. This program is expected to serve as a sustainable model for disaster mitigation education, particularly to enhance public awareness of the importance of earthquake preparedness.